Scientific fraud. A disease we find among ourselves. - Guimarães, S (1998)
Scientific fraud is not a problem exclusive to countries with high scientific development. Fraud does not necessarily mean invention of results, usurpation of ideas, manifest plagiarism or any other kind of serious scientific misconduct. Although more rare in countries where scientific production is more modest, pungent cases of scientific fraud also exist. However, less notorious cases of scientific misconduct are frequent and must be avoided. Examples of these less notorious sins are presented. The seriousness of scientific fraud is not only due to the fact that it may involve public funds, which could have been put to more useful purposes but, above all, because it violates scientific ethics and frustrates the final aim of science, the discovery of truth.